No evidence for prolonged latency of saccadic eye movements due to intermittent light of a CRT computer screen. - Jainta S; Jaschinski W; Baccino T (Ergonomics, 2004)
Despite previous studies it remains unclear, whether saccadic eye movements across computer screens may be adversely affected by the intermittency of light of cathode ray tubes (CRT). We measured the latency of simple saccades to peripheral targets presented on a CRT-screen, operated at refresh rates of 50, 100 and 150 Hz, compared with a special fluorescent lamp display (FLD). Our results suggest that the intermittent light of CRT screens does not prolong the latency of saccades not even relative to a control condition of unmodulated steady light at the FLD. Further, there was no evidence for any individual effect in possibly susceptible subjects, e.g. at high critical flicker frequencies (CFF).